2005
DOI: 10.1080/00071660500191098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial phytase on production performance of White Leghorn layers fed on a diet low in non-phytate phosphorus

Abstract: 1. An experiment with 150 White Leghorn layers was conducted to examine the effect of microbial phytase supplementation of low non-phytate phosphorus (NPP) diets on egg production, eggshell quality, bone mineralisation and retention of nutrients at 32-48 weeks of age. 2. Four isonitrogenous and isocaloric diets were formulated to contain 1.2, 1.8, 2.4 and 3.0 g NPP/kg diet with the two lowest NPP (1.2 and 1.8) supplemented with microbial phytase (Biofeed Phytase, India) at 500 FTU per kg diet. Each diet was of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 22 publications
(32 reference statements)
3
16
1
Order By: Relevance
“…In line also with the present results, Lim et al (2003) observed that phytase supplementation decreased the percentage of broken and soft-shell eggs. In contrast to the present results, Panda et al (2005) stated that neither MP supplementation nor decreasing NPP level (from 0.30-0.18%) in laying hen diets had a significant effect on egg quality traits (egg weight, Haugh units, shell weight, shell thickness, shell strength or egg specific gravity). Other investigators also failed to find positive effects of MP on percentages of egg yolk and egg albumen (Mohammed et al, 2010), shell thickness, egg specific gravity, yolk index and Haugh units (Afsari et al, 2013), eggshell quality (Musilova et al, 2014) or on all egg quality traits investigated (Lucky et al, 2014).…”
Section: Components (%) ------------------------------------------------contrasting
confidence: 55%
“…In line also with the present results, Lim et al (2003) observed that phytase supplementation decreased the percentage of broken and soft-shell eggs. In contrast to the present results, Panda et al (2005) stated that neither MP supplementation nor decreasing NPP level (from 0.30-0.18%) in laying hen diets had a significant effect on egg quality traits (egg weight, Haugh units, shell weight, shell thickness, shell strength or egg specific gravity). Other investigators also failed to find positive effects of MP on percentages of egg yolk and egg albumen (Mohammed et al, 2010), shell thickness, egg specific gravity, yolk index and Haugh units (Afsari et al, 2013), eggshell quality (Musilova et al, 2014) or on all egg quality traits investigated (Lucky et al, 2014).…”
Section: Components (%) ------------------------------------------------contrasting
confidence: 55%
“…Beneficial effects of dietary phytase supplementation on egg production, feed intake and egg weight of laying hens have been reported (Panda et al, 2005, Hughes et al, 2008, Kozłowski and Jeroch, 2011, Valaja et al, 2013. In these studies, phytase was added to negative control diets with reduction of only P, not with reduction of Ca, dig AA and energy.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing egg production as a result of tested enzyme supplementation may be due to that phytate presented in the most ingredients of poultry diet is capable of forming complexes with essential nutrients such as proteins and some inorganic cations. The use of phytase may release these essential nutrients thereby improving nutritional value of poultry diet, which resulted positively on productive performance of laying hens (Panda et al 2005). The response to the enzyme is not straightforward since it is relatively variable, depending upon factors such as bird age and type (Scott et al 2001), cereal grains, level and geographical locations (Chesson 2001), enzyme inclusion level (Karimi et al 2000) and feed processing (Svihus et al 2000).…”
Section: Resultsmentioning
confidence: 99%